PSYCHOLOGICAL FEATURES OF MORAL EDUCATION - Baktybay kyzy S. (Vestnik Issyk-Kulʹskogo universiteta)
This article examines the features of moral education, focusing on the role of the family and parents in shaping a child’s moral qualities. The importance of cultivating moral norms and values such as honesty, fairness, magnanimity, responsibility, conscience, humanity, discipline, respect for elders, care for younger ones, love for work, patriotism, respect for national symbols, adherence to law, fulfillment of civic duties, and compassion is particularly emphasized. The significance of instilling ethical values, moral awareness, and motivation in children within the framework of school and family is also highlighted.The article notes that education in modern schooling is the second main function of child socialization, following learning. Moral education plays a crucial role in preparing children for public life and helping them gain life experience. It stresses the need for systematic influence on the child through educational measures aimed at developing their abilities during the learning process, forming their personality, and shaping their relationship with the world, society, and those around them.